The Use of L-Moments in Modelling of Deprivation of the Population Aged over 50 in the Czech Republic - Malá, Ivana (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
In the Survey of Health, Ageing and Retirement in Europe (SHARE) the European population aged over 50 is of interest; SHARE provides a multidisciplinary approach that delivers the comprehensive picture of the ageing process in Europe. In the fifth wave of the survey (carried out in 2013) two composite indicators of deprivation are evaluated. The answers to the selected questions (11 items for the material deprivation index and 15 items for the social deprivation index) from the survey are weighted into two composite indices with values transformed to the interval from 0 to 1. In the contribution, the empirical distributions of these indices in the Czech Republic are analysed and dependence on gender and size of household is treated. A mixture of two normal distributions for social inclusion index and a mixture of one discrete and two normal distributions for the index of material deprivation are fitted into the data. The models identify two homogenous subpopulations for social deprivation index and for positive values of material deprivation. 40 percent of respondents without any material deprivation were found in our data in comparison with less than 1 percent for the social deprivation index. Maximum likelihood estimates are compared to estimates obtained by the moment method based on robust moments
20-th AMSE. Applications of Mathematics and Statistics in Economics. International Scientific Conference: Szklarska Poręba, 30 August- 3 September 2017. Conference Proceedings Full Text Papers, s. 285-296
Keywords: deprivation; SHARE data; finite mixture of distributions; L-moments